Fat as a fuel: emerging understanding of the adipose tissue-skeletal muscle axis. - Frayn, K (2010)
The early pioneers in the field of metabolism during exercise such as Lindhard and Krogh understood the importance of fat as a fuel for muscle contraction. But they could not have understood the details of the pathways involved, as neither the metabolic role of adipose tissue nor the transport role of non-esterified fatty acids (NEFA) in the plasma was clearly understood at the time. We now recognize that the onset of muscular contraction coincides with an increase in the delivery of NEFA from adipose tissue, probably coordinated by the sympatho-adrenal system. During light exercise, adipose tissue-derived NEFA make up the majority of the oxidative fuel used by muscle. As exercise is prolonged, the importance of NEFA increases. The onset of exercise is marked by an increased proportion of NEFAs entering beta-oxidation rather than re-esterification and recycling. At moderate intensities of exercise, other sources of fat, potentially plasma- and intramyocellular-triacylglycerol, supplement the supply of plasma NEFA. The delivery of NEFA is augmented by increased adipose tissue blood flow and by other stimuli such as atrial natriuretic peptide. Only during high-intensity exercise is there a failure of adipose tissue to deliver sufficient fatty acids for muscle (which is coupled with an inability of muscle to use them, even when fatty acids are supplied artificially). This limitation of adipose tissue NEFA delivery may reflect some feedback inhibition of lipolysis, perhaps via lactate, or possibly alpha-adrenergic inhibition of lipolysis at very high catecholamine concentrations.